Tomie Ohtake memória e gesto: inferências sobre o zen e o abstracionismo informal através das pinturas cegas (1958-1962) - Faria, Daniela Cristina [UNIFESP] (2020)
Tomie Ohtake (1913-2014), Japanese-Brazilian painter and sculptor, has in her curriculum more than 20 International Biennials. Her works are constantly pointed out as related to Zen aesthetics, one of the Buddhist strands of Japan. For this line of thought, art can be considered a form of meditation, both for the artist and the viewer. It is necessary, however, to understand that Zen is the most widespread Buddhist aspect in the West, although it is only one of the branches of religion absorbed by Japanese society throughout history. In another perspective, this research takes into account that significant changes occurred in the artistic scene of several countries, and that abstract art began to be frequently appreciated in the period after the Second World War. Moment in which Tomie Ohtake started her artistic life from 1952. On the one hand, several avant-garde emerged in Japan who found in abstractionism the best way to express their “cry for liberation”, with emphasis on the informal movement. On the other hand, the West saw with fascination a sensitivity and depth in Japanese arts, which differed from what had been seen in America and Europe until then. For this research, we selected 20 works by Ohtake blindfolded, between 1958 and 1962, entitled Blind Paintings. In order to seek a better understanding of her Japanese memories expressed through gesture and intuition, in which there may be traces of Zen as part of her cultural roots. We do not disregard that Informalism had a strong presence among Brazilian artists of Japanese origin from the same period, that is why we seek to broaden the look through correlations between the context of her artistic development and her Japanese origin.